2019
DOI: 10.1299/mej.18-00498
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic model of muscle fatigue and recovery considering the roles of slow-twitch and fast-twitch muscles (Validation with a pulling motion)

Abstract: Dynamic model of muscle fatigue and recovery considering the roles of slow-twitch and fast-twitch muscles (Validation with a pulling motion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the present chapter, the musculoskeletal model considering the role of antagonistic muscle pairs proposed by Oshima et al (1999) is first explained. The muscle fatigue and recovery model considering the different behaviors of ST and FT fibers previously proposed by our research group (Miura et al, 2019) is then explained in section 2.2. Finally, the method of predicting the degree of fatigue of each muscle in the arm proposed in the present study is described in section 2.3.…”
Section: Model Of Muscle Fatigue and Recovery Considering The Roles Of Antagonistic Musclesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present chapter, the musculoskeletal model considering the role of antagonistic muscle pairs proposed by Oshima et al (1999) is first explained. The muscle fatigue and recovery model considering the different behaviors of ST and FT fibers previously proposed by our research group (Miura et al, 2019) is then explained in section 2.2. Finally, the method of predicting the degree of fatigue of each muscle in the arm proposed in the present study is described in section 2.3.…”
Section: Model Of Muscle Fatigue and Recovery Considering The Roles Of Antagonistic Musclesmentioning
confidence: 99%
“…Our research group proposed the model shown in Fig. 3 for the prediction of muscle fatigue and recovery considering the roles of ST and FT fibers (Miura et al, 2019). As before, the muscle is considered to consist of M0 total motor units.…”
Section: Muscle Fatigue and Recovery Model Considering Slow-and Fast-twitch Musclesmentioning
confidence: 99%
See 2 more Smart Citations